2004
DOI: 10.1002/vnl.20025
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐year durability of a 20‐mil PVC geomembrane

Abstract: In 1971, twenty circular aquaculture ponds were constructed for the W. K. Kellogg Biological Research Station in Hickory Corners, Michigan. The 30.5‐m‐diameter research ponds were lined using a 0.51‐mm‐thick fish‐grade PVC geomembrane. Over the years the ponds became congested with dense, persistent stands of cattails, trees, and other vegetation, which required the ponds to be cleared and relined in September 2000 in order to allow the initiation of new experiments. The lack of holes in the exhumed geomembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thus it is important to evaluate the field performance of factory seams. Recent research shows that factory seams also perform well in thinner PVC geomembranes (0.51 mm) over even longer periods of exposure (,30 years) than studied in this project (Newman et al 2004).…”
Section: Hydrostatic Resistancementioning
confidence: 60%
“…Thus it is important to evaluate the field performance of factory seams. Recent research shows that factory seams also perform well in thinner PVC geomembranes (0.51 mm) over even longer periods of exposure (,30 years) than studied in this project (Newman et al 2004).…”
Section: Hydrostatic Resistancementioning
confidence: 60%
“…However a GCL and/or a CCL overlain by an intact HDPE geomembrane are protected from root penetration. Intact HDPE geomembranes are impervious to roots and cause roots to follow laterally atop the geomembrane surface (Landreth 1991;Carson 2001;Serrato 2004;Newman et al 2004).…”
Section: Gcl Divalent Cation Exchangementioning
confidence: 99%
“…An investigation conducted by Serrato (2004) at SRS showed that roots from overlying pine trees turned horizontally and followed along the top of the geomembrane upon reaching a HDPE geomembrane without damaging or penetrating it. Newman et al (2004) describe the thirty-year durability of a 20-mil thick polyvinylchloride (PVC) geomembrane used as an aquaculture pond liner. They interpreted the lack of holes to indicate resistance to both microorganisms and root penetration from the dense stand of cattails, trees, and other vegetation.…”
Section: Biological Degradation (Microbial Root Penetration Burrowing Animals)mentioning
confidence: 99%